Analisis Kepuasan Pasien COVID-19 di RSUD Dr. H. Ibnu Sutowo Baturaja Kabupaten Ogan Komering Ulu - Rynna Dyana; Chairil Zaman (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2023)
At the beginning of 2020, Indonesia experienced the attack of COVID-19 which became a world pandemic. A special location is prepared as a place for handling COVID-19 patients along with health personnel resources, and supporting facilities. As the location for the treatment of COVID-19 patients, it is necessary to know the satisfaction response of patients who have been treated at the Emergency Hospital of RSUD dr. H. Ibnu Sutowo Baturaja with the hope that it can be useful for good service quality in hospitals. This study is a qualitative research with data collection methods through in-depth interviews with COVID-19 patients who have received treatment at Emergency Hospitals, Emergency Hospital nurses, and Management at dr. H. Ibnu Sutowo, supported by observation and documentation. The results show that the factors that make COVID-19 patients treated at the Emergency Hospital satisfied are friendly doctors and nurses, good service, easy-to-understand explanations, motivation that is always given by officers and adequate infrastructure. The service procedure is considered good. There are no significant obstacles when the patient is treated. The quality of care was considered satisfactory. The infrastructure is adequate. Health protocols have been implemented. Communication, friendliness, politeness, skills, and responsiveness were felt quite well. Based on this research, it is expected that Emergency Hospital officers will continue to maintain and improve service quality. Hospitals are expected to improve and maintain infrastructure and assess patient satisfaction on a regular basis. The government is expected to continue to increase supervision and support for referral hospitals that treat COVID-19 patients.